(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: What is the biomorphological structure of flora of the classes of the ruderal vegetation of Ukraine? Locations: Ukraine. Materials and methods: field research, comparative-structural analysis, detailed route geobotanical. Nomenclature: Mosyakin & Fedoronchuk 1999, Dubyna et al. 2019. Results: The analyzed biomorphological structure of the coenoflora of the ruderal vegetation of Ukraine according to Raunkiær’s life form system, represented by the classes Stellarietea mediae, Artemisietea vulgaris, Bidentetea, Galio-Urticetea, Plantaginetea majoris, Polygono-Poëtea annuae, Robinietea, Epilobietea angustifolii, has 1475 species of vascular plants belonging to 570 genera and 116 families, which includes hemicryptophytes 705 species (47.8 %), therophytes 355 (24.1 %), cryptophytes 253 (17.1 %), phanerophytes 135 (9.2 %), chamaephytes 28 (1.9 %). It was established, that ten leading families make up 60 % of the entire flora of ruderal vegetation. They are represented by hemicryptophytes – 478 species, or 55.8 % of their total number, therophytes – 346 (23.4 %), cryptophytes – 126 (8.5 %), phanerophytes – 45 (3.1 %) and chamaephytes – 12 (0.8 %). A comparison of the number of species of different life forms in the classes of ruderal vegetation is given. The highest percentage of phanerophytes was in the Robinietea class, chamaephytes – Stellarietea mediae, hemicryptophytes – Plantaginetea majoris, cryptophytes – Bidentetea, therophytes – Polygono-Poëtea annuae. The dendrogram of the similarity/dissimilarity of species of the considered classes by life forms consists of 3 groups of clasters formed by ecotopes of coenoflora of the classes Stellarietea mediae and Artemisietea vulgaris (first group), Galio-Urticetea and Robinietea (second), Polygono-Poëtea annuae and Plantaginetea majoris, Bidentetea and Epilobietea angustifolii (form two subgroups in the third group). Among the particularly dangerous invasive alien species of plants found in the coenoflora of ruderal vegetation are 8 phanerophytes, 5 hemicryptophytes, 3 cryptophytes, and 15 therophytes. The most widespread species of alien invasive plants in the ruderal coenoflora include 8 phanerophytes, 3 hemicryptophytes, 1 cryptophyte, and 6 therophytes. There are 12 rare species in the ruderal coenoflora, among them one phanerophyte (Tamarix gracilis), eight hemicryptophytes (Linaria biebersteinii, Vincetoxicum rossicum, Senecio borysthenicus, Otites artemisetorum, Chrysopogon gryllus, Stipa capillata, S. lessingiana, S. pulcherrima), two cryptophytes (Agropyron cimmericum, Orchis picta), and one therophyte (Tragopogon borysthenicus).